2014
DOI: 10.1097/mot.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for cholangiocarcinoma

Abstract: The poor outcome of cholangiocarcinoma, irrespective of the therapy, justifies the search for novel approaches. Only selective patients with perihilar cholangiocarcinoma subjected to a neoadjuvant protocol may qualify for liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 37 publications
0
9
0
2
Order By: Relevance
“…CCA usually metastasize and cause relapse because it is commonly diagnosed in the advanced stage of the disease, and leads to poor prognosis [2][3][4]. Many studies have revealed that numerous genes are involved in CCA [5][6][7][8][9] and many therapeutic strategies have been developed to treat CCA [10][11][12]; however, the survival rate for CCA patients is still low [13]. In this case, the pathogenesis and progression of this malignancy remains to be investigated and new therapeutic targets need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…CCA usually metastasize and cause relapse because it is commonly diagnosed in the advanced stage of the disease, and leads to poor prognosis [2][3][4]. Many studies have revealed that numerous genes are involved in CCA [5][6][7][8][9] and many therapeutic strategies have been developed to treat CCA [10][11][12]; however, the survival rate for CCA patients is still low [13]. In this case, the pathogenesis and progression of this malignancy remains to be investigated and new therapeutic targets need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…75 Orthotopic liver transplantation failed as therapeutic approach for cholangiocarcinoma due to its unfavorable biology. 76 In 2002, Slakey published the first case of RFA in ICC, performing ablation and surgery in recurrent disease after liver surgery. 77 Similar case reports from various working groups followed in the next years.…”
Section: Intrahepatic Cholangiocellular Carcinomamentioning
confidence: 99%
“…Only 29% of these patients were surgical candidates, and in the subgroup of the remaining patients with stage I disease RFA was the only treatment strategy with improved survival (17). Orthotopic liver transplantation (OLT) is not considered to be a standard therapeutic approach for localized cholangiocarcinoma (18).…”
Section: Introduction Introductionmentioning
confidence: 99%